Analisis Potensi Sektoral Ekonomi Di Kabupaten Belu - Charles Cha Amteme (Ekopem: Jurnal Ekonomi Pembangunan, 2021)
ABSTRACT Charles Amteme, NPM: 42150013 "Analysis of Economic Sectoral Potential in Belu Regency" under the guidance of Mr. Prof.Dr. Sirilius Seran, SE.MS as supervisor I and Mr. Frederich W. Nalle, SE.ME as supervisor II. The problem raised from this study is how the sector shifts to the economy in Belu District and whether there are leading sectors in the economy in Belu District. The objectives to be achieved in this study are to determine the Sector Shift to the economy in Belu District and to find out whether there is a superior Sector in the economy in Belu Regency. The data used in this study are secondary data obtained from the Central Statistics Agency Office in Belu Regency. The data analysis technique used is the Shift Share analysis and Klassen Typology. Based on the results of shift share analysis, the sector that has the largest national share value is the agricultural sector, while the smallest value is in the electricity and gas and clean water sectors. According to the proportional shift analysis it is known that there are six sectors in Belu Regency whose growth is slower ompared to the NTT province, namely: agriculture, mining and grazing, the manufacturing industry sector, the electricity gas and water supply sector, the hotel and restaurant trade, and the sector finance, leasing and corporate services. While the differential shift analysis is known that there are four sectors in Belu Regency that grow faster based on internal locational factors, namely: the mining and mining sector, the manufacturing sector, the electricity, gas and water supply sector and also the transportation and communication sector. Based on the results of the typology analysis, the sectors included in the developed and rapidly growing sectors are other service sectors. Meanwhile, the sectors included in the advanced but depressed sectors are the financial sector, leasing and corporate services. Sectors classified as potential or still developing sectors are: agriculture and the relatively backward or underdeveloped sectors are the mining and quarrying sector, the processing industry, gas electricity and drinking water, construction, the restaurant and hotel trade and the communication and transportation sector.